2019
DOI: 10.1177/0890334419837523
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin and Dermcidin in Human Milk and Their Alteration in Gestational Diabetes

Abstract: Background: Chemerin and dermcidin, which have antimicrobial properties, are molecules that are also related to insulin resistance and inflammation. Research aims: The aims were to determine the amounts of chemerin and dermcidin in the milk and blood of mothers with gestational diabetes, and to compare the amounts of chemerin and dermcidin in the milk and blood of mothers with and without diabetes. Methods: This was a two-group nonrandomized longitudinal study with a convenience sampling of mothers without ges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…Furthermore, chemerin concentrations in maternal milk were increased compared with values determined in peripheral blood. Mothers with GDM had significantly higher levels in their milk compared with controls [196].…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 87%
“…Furthermore, chemerin concentrations in maternal milk were increased compared with values determined in peripheral blood. Mothers with GDM had significantly higher levels in their milk compared with controls [196].…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 87%
“…Thereafter, a hydrophobic messenger peptide, consisting of 20 amino acids, is detached, while the produced proprotein is released from the cell. Proteases are responsible for the activation and formation of the final form of chemerin [ 54 ]…”
Section: Biomoleculesmentioning
confidence: 99%
“…Chemerin mRNA has been detected in many animal species, including humans, rodents, bovine, and poultry [ 55 ]. In humans, it is produced mainly by white adipose tissue (visceral and subcutaneous), liver, and placenta and to a lesser extent by brown adipose tissue, lungs, skeletal muscles, kidneys, ovaries, heart, and adrenal glands [ 54 , 55 , 56 , 57 ]. Its physiological functions involve regulation of blood pressure, immune functions, angiogenesis, and inflammation [ 58 ].…”
Section: Biomoleculesmentioning
confidence: 99%
“…Ustebay et al analyzed Chemerin and Dermicin in all phases of lactation and found that these are significantly increased by GDM; moreover, the highest amount was found in the colostrum and the lowest in mature milk [25].…”
Section: Anti-infective Proteinsmentioning
confidence: 99%